Wellbeing and Tourism: A Bibliometric Analysis - Peri Antari, Ni Putu; Indra Yoga Pratama, I Putu; Prastyadewi, Made Ika (Admisi dan Bisnis, 2024)
The development of the tourism sector is closely related to the participation of the community around the tourist area. Then, the welfare of the surrounding community is a driving factor for the success of the tourism development. This study aims to investigate the breadth of research on public welfare and the tourism sector. This study uses a quantitative method based on bibliometric analysis using VOSViewer. Data obtained through the Scopus database with a total of 182 documents. The results showed that research with the keyword community wellbeing has a close relationship with tourism and tourism development. Meanwhile, in the context of community in tourism, namely health status, food security, social capital, life satisfaction, agriculture workers and environmental protection, it still needs to be studied more deeply. Even though tourism is the mainstay of Bali's development and economy, its development creates its own problems, especially for natural resources, the environment and creates anxiety for the community, especially related to income inequality